Sliding mode control of grid-tied single-phase inverter in a photovoltaic MPPT application. (October 2017) - Cortajarena, José Antonio; Barambones, Oscar; Alkorta, Patxi; De Marcos, Julián
Highlights: A new Sliding Mode Controller was used to regulate the inverter voltage for PV MPPT. The Sliding Mode Controller showed good dynamic behavior and disturbance rejection. PV was directly connected to a single-phase grid tied inverter to improve its efficiency. Experimental validation of the SMC controller showed the expected robustness. Abstract: This paper presents the design and experimental validation of a new Sliding Mode Controller (SMC) for a single-phase grid-tie inverter in a photovoltaic (PV) Maximum Power Point Tracking (MPPT) application. The number of PV modules required in the string is determined to meet the voltage requirements of the grid-connected inverter, this way the PV modules are connected directly to the DC link of the inverter in a centralized topology and the high step-up power converter of the conventional systems is avoided, obtaining a higher efficiency. The used MPPT algorithm is the hill climbing or perturbation–observation (P&O) and a new Sliding Mode Controller is used to regulate the desired inverter voltage according to the MPPT algorithm. SMC allows to avoid the need of an exact knowledge of the system parameters and offers many desirable properties, such as good performance against no modelled dynamics, insensitivity to parameter variations, and an excellent external disturbance rejection. The inverter control has been designed in the d-q rotating reference frame after use a virtual bi-phase system. Several experimental tests have been carried out in suitable and adverse conditions, concluding that the presented system provides an efficient maximum power tracking.